The Impact of Ecological Civilization Theory on University Students’ Pro-environmental Behavior: An Application of Knowledge-Attitude-Practice Theoretical Model - Wang, Kuan; Zhang, Lu (Frontiers in Psychology, 2021)
In environmental education, environmental knowledge is considered to be one of the most important factors affecting university students’ pro-environmental behavior. First, in this paper, the ecological civilization theory (ECT) was understood as a new kind of environmental knowledge. Based on this, a new theoretical model for analyzing the relationships among environmental knowledge, environmental attitude, and environmental behavior was designed in this paper according to ECT and the Knowledge-Attitude-Practice (KAP) theoretical model. Second, from the perspective of students, a questionnaire was designed for students according to ECT, so as to understand the level of ECT of students. On this basis, an empirical test of the relationship between the ECT level, pro-environmental attitude level, and pro-environmental behavior level was carried out. This research shows that ECT as environmental knowledge is as important as science-oriented environmental knowledge (SEK) in environmental education. As a result, the role of environmental knowledge in environmental education should not be ignored but environmental knowledge should be enriched by adding ECT to the environmental knowledge system and improving the environmental knowledge education curriculum, contributing to environmental education in China.